Yamato-82162: A new kind of CI carbonaceous chondrite found in Antarctica - Tomeoka, Kazushige; Kojima, Hideyasu; Yanai, Keizo (National Institute of Polar Research, 1989)
P(論文) A petrographic and mineralogical study of the Yamato-82162 (Y-82162) meteorite shows that it may be the first CI carbonaceous chondrite that has ever been found in Antarctica. Y-82162 consists largely of fine-grained, phyllosilicaterich matrix and contains a large amount of Ni-bearing pyrrhotite and small amounts of framboidal, platy, spheroidal, and anhedral magnetite, Mg-Fe-rich carbonates, and Ca-phosphate. Isolated clusters of coarsely crystallized phyllosilicates are also present. The presence of these minerals supports the idea that Y-82162 is a CI carbonaceous chondrite. However, this meteorite shows several mineralogical features that apparently differ from non-Antarctic CI chondrites : it has much higher abundances of coarse phyllosilicates and pyrrhotite than non-Antarctic CI chondrites, and has no veins of sulfates and carbonates, suggesting that it was derived from different primary materials and has experienced a different aqueous alteration history from non-Antarctic CI chondrites. The Y-82162 matrix also contains abundant fine grains of olivine, which contrasts with non-Antarctic CI chondrites. The textures suggest that matrix phyllosilicates were dehydrated and altered to olivine by heating. Thus, this meteorite probably has been affected by mild thermal metamorphism. These results indicate that Y-82162 has experienced a distinct late history from the non-Antarctic CI chondrites, suggesting that it may have been derived from a different source from that of non-Antarctic CI chondrites. departmental bulletin paper